Phenotypes and outcomes in middle-aged patients with diabetic foot ulcers: a retrospective cohort study - Tao Tong; Cailian Yang; Wenqing Tian; Zhiping Liu; Bo Liu; Jun Cheng; Qingfeng Cheng; Bo Zhou (Journal of Foot and Ankle Research, 2020)
Abstract Background Although ageing could increase the risk of delayed healing in diabetic foot ulcers (DFUs) patients, data from middle-aged patients remains greatly limited. The purpose of this study was to explore the clinical phenotypes, outcomes and predictive factors of DFU in middle-aged patients. Methods A retrospective cohort study conducted with 422 consecutive inpatients with DFUs who visited our hospital between May 2010 and September 2017; participants were recruited and assigned according to age to either the middle-aged group or the elderly group. The Demographics, ulcer characteristics, comorbidities and diabetes complications, laboratory tests, socioeconomic data and final outcomes were collected. Moreover, predictive factors of adverse outcomes in middle-aged DFUs patients were assessed. Results Middle-aged patients were more likely to have worse lifestyle and glucose control, were more likely to have microangiopathy as a complication, and tended to have larger and deeper ulcers; however, these patients also had higher rates of healing and lower rates of mortality and major amputaion than elderly patients. Severe infection,living alone,current smoking cigarettes, and having a high white blood cell count were independent risk factors for adverse outcomes in middle-aged patients. Conclusions DFUs are relatively common in middle-aged patients with diabetes, and these patients have unique clinical phenotypes and risk profiles. Nonetheless, further investigation is needed to clarify whether intervention targeting these easily recognizable risk factors can improve healing and survival rates in middle-aged DFU patients.